A high-throughput and untargeted lipidomics approach reveals new mechanistic insight and the effects of salvianolic acid B on the metabolic profiles in coronary heart disease rats using ultra-performance liquid chromatography with mass spectrometry. Issue 29 (1st May 2020) - Li, Ying-peng; Wang, Cong-ying; Shang, Hong-tao; Hu, Rui-rui; Fu, Hui; Xiao, Xue-feng
Abstract : High-throughput lipidomics provides the possibility for the development of new therapeutic drugs. Abstract : High-throughput lipidomics provides the possibility for the development of new therapeutic drugs. Accordingly, herein, we reveal the protective role of salvianolic acid B (Sal B) in rats with coronary heart disease (CHD) and propose a new mechanism for its action through a high-throughput and non-targeted lipidomics strategy. A CHD animal model was induced by consecutive high-fat diet feeding with vitamin D3 injection. At the end of the 8th week, the serum sample was analyzed to explore the metabolic biomarker and pathway changes using untargeted lipidomics based on ultra-performance liquid chromatography with mass spectrometry (UPLC/MS). In addition, blood and heart tissue samples were collected and processed for the detection of biochemical indicators and liver histological observation. After salvianolic acid B treatment, the levels of LDH, CK, CK-MB, MYO, CTn1, TG, TC, LDL-c, and Apo(b) were significantly lower than that in the model group, while the levels of HDL-c and Apo(a1) were significantly higher than that in the model group. Furthermore, the histological features of fibrosis and steatosis were also evidently relieved in the model group. A total of twenty-six potential biomarkers were identified to express the lipid metabolic turbulence in the CHD animal models, of which twenty-two were regulated by salvianolic acid B trending to the normal state, including TG(20:0/20:4/o-18:0), PC(20:4/18:1(9Z)), PC(18:3/20:2), PA(18:0/18:2), LysoPE(18:2/0:0), SM(d18:0/22:1), PE(22:6/0:0), LysoPE (20:4/0:0), sphinganine, Cer(d18:0/18:0), PS(14:0/14:1), PC (18:0/16:0), LysoPC(17:0), PE(22:2/20:1), PC(20:3/20:4), PE(20:4/P-16:0), PS(20:3/18:0), cholesterol sulfate, TG(15:0/22:6/18:1), prostaglandin E2, arachidonic acid and sphingosine-1-phosphate. According to the metabolite enrichment and pathway analyses, the pharmacological activity of salvianolic acid B on CHD is mainly involved in three vital metabolic pathways including glycerophospholipid metabolism, sphingolipid metabolism and arachidonic acid metabolism. Thus, based on the lipidomics-guided biochemical analysis of the lipid biomarkers and pathways, Sal B protects against CHD with good therapeutic effect by regulating glycerophospholipid metabolism, sphingolipid metabolism and arachidonic acid metabolism, inhibiting oxidative stress damage and lipid peroxidation.